Vocal tract shaping of emotional speech. (November 2020) - Kim, Jangwon; Toutios, Asterios; Lee, Sungbok; Narayanan, Shrikanth S.
Highlights: A database of real-time MRI data from ten actors enacting four different emotions is made available to the research community. Happy and angry speech display greater articulatory movement range compared to neutral speech. Happy speech displays shorter vocal tract length compared to angry, sad, or neutral speech. In the production of low vowels, happy speech displays smaller opening of the front oral cavity compared to angry and happy speech. Abstract: Emotional speech production has been previously studied using fleshpoint tracking data in speaker-specific experiment setups. The present study introduces a real-time magnetic resonance imaging database of emotional speech production from 10 speakers and presents articulatory analysis results of speech emotional expression using the database. Midsagittal vocal tract parameters (midsagittal distances and the vocal tract length) were parameterized based on a two-dimensional grid-line system, using image segmentation software. The principal feature analysis technique was applied to the grid-line system in order to find the major movement locations. Results reveal both speaker-dependent and speaker-independent variation patterns. For example, sad speech, a low arousal emotion, tends to show smaller opening for low vowels in the front cavity than the high arousal emotions more consistently than the other regions of the vocal tract. Happiness shows significantly shorter vocal tract length than anger and sadness in most speakers. Further details of speaker-dependent and speaker-independent speech articulation variation in emotional expression and their implications are described.